Controlled release of poorly water soluble anticancerous drug camptothecin from magnetic nanoparticles. (2020) - Patil, A.R.; Nimbalkar, M.S.; Patil, P.S.; Chougale, A.D.; Patil, P.B.
Abstract: The bioavailability of poorly water-soluble anticancerous drug camptothecin (CPT) was improved by its conjugation with magnetic nanoparticles (MNPs). For this the surface of MNPs was modified by (3-aminopropyl)triethoxysilane (APTES) to obtain free amino groups at the end. These surface modified MNPs (MNP-APTES) were used for drug loading. Bare MNPs and MNP-APTES were characterized by X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy, Field Emission Scanning Electron Microscopy (FESEM) and Vibrating Sample Magnetometer (VSM). The loading and release behavior of CPT from MNP-APTES was also investigated.